Immigrant’s Cultural Alienation in Elaine Chiew’s Face - Sari, Tribuana; Hartati, Nariswari; Trisnawati, Ririn Kurnia; Hadiningrum, Indriyati (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
This research focuses on the cultural alienation of an elderly Chinese immigrant narrated in Elaine Chiew’s Face (2019). Face is a story that highlights the life of Yun, an elderly Chinese woman who moves to London and feels alienated from her surroundings. To analyze the data, the descriptive qualitative method and Seeman’s theory of alienation (1959) are employed. This research discovers that alienation undergone by elderly can be resulted from powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. Powerlessness rises when the elderly immigrants could not cope with bullying problem, while feeling meaninglessness comes from their inability in doing productive activities like what they had in their home-land. Incapability to adapt with the culture, norms, and values in the host-country results in their normlessness detaching them more from their surroundings. It worsens due to the language barrier, no same-aged friends, and geriatric bladder issues. Lastly, their social functions that do not work well lead them into self-estrangement. The findings of this research show that cultural alienation experienced by elderly immigrants could lead them into identity crisis.